Optimizing Ground Handling Operations to Enhance Service Efficiency at Airports - A Literature Review - Nasser Ali Rashid AlMataani; Dr. Naim Ayadi (IJRDO - Journal of Business Management, 2025)
Ground handling operations are critical components of the air transport industry, influencing overall efficiency, safety, and customer satisfaction at airports. This literature review explores current research and advancements in optimizing ground handling operations to enhance service efficiency. It synthesizes findings from diverse studies on process improvement, technological integration, workforce management, and sustainability. The review identifies key challenges and future directions, emphasizing the importance of a holistic and technology-driven approach to optimize these essential airport functions.